Interpretation of the Symbolics and Meaning of three in the Unique Fresco Icon of Three-Handed Virgin Mary and the older Sanctification of the St. Trinity church in Karan - Andrejić, Živojin R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In the church devoted to Presentation of Virgin Mary in Karan there is a monumental fresco icon preserved until today representing Three-handed Virgin Mary, the one of a kind in Byzanthine-Orthodox style. This icon can be a good model for reconstructing the icon of the same name in the church devoted to Three-handed Virgin Mary in Skoplje in which her cult was established as late as in1204 and renewed by the Serbian king Milutin in 1300. The nun in the deep bow showed in the painting by the legs of Three-handed Virgin Mary in White Church in Karan is the patron of the painting located in a niche formed in a subsequently partitioned south arcade of the iconostatis about the year 1354. The painting of the Three-handed Virgin Mary is related to the fact that the church in Karan was later dedicated to her and obviously connected to an important event during the reign of emperor Dusan. It can also be speculated that it was because of making the church of Three-handed Virgin Mary the seat of the Skopje diocese and its raising to the rank of metropolis of the first degree by emperor Dusan in 1346, presumably on June 28. The church could have memorised a major event related to emperor Dusan and his father, possibly on June 28, 1355 when he successfully ended the war against Hungarian king Ludwig I. There is also a possibility that it was devoted to the day when the daughter of prefect Brian was made a nun in the monastery in Karan in which she would spend the rest of her life and be buried as well, according to her own will and intention. Revealing the tomb in front of Three-handed Virgin Mary confirms the funerary purpose of this fresco icon. The painting of the Virgin Mary’s third hand was made according to the universal understanding of the Son by the Mother ’You are my other (left) hand’. The three-handedness of Virgin Mary has its analogy in the three-headed representations of archangels and Christ in the Eastern-orthodox areas as a way of giving praise to one aspect of St. Trinity. The Three-handed Virgin Mary symbolises one specific aspect of the triple divine power of St. Trinity embodied through Christ. The confirmation for sanctification of St. Trinity church in Karan are also huge get-togethers held on Rosulje by the port of the church from 18th-20th century during the Spirits – ’the second day of the St. Trinity’s holiday’. The churches and the names of the places nearby – Rosulje, Rusalija, Rusinica, Ruzica – clearly imply on the long gone monasteries and churches devoted to St. Trinity. The Day of Three-handed Virgin Mary is was celebrated on June 28th in the middle-ages, but for some unknown reasons, people stopped celebrating it. It also disappeared from the orthodox church’s calendar. The reason might be switching to celebrating St. Trinity.
Keywords: Rosulje; St. Trinity church in Karan; Three-handed Virgin Mary